2022
DOI: 10.51731/cjht.2022.487
|View full text |Cite
|
Sign up to set email alerts
|

Liposuction for Lymphedema

Abstract: Liposuction with controlled compressive therapy was associated with higher volume reduction compared with controlled compression therapy alone. This finding was from a low- to moderate-quality meta-analysis of 2 prospective cohort studies. The certainty of the evidence is very low. Liposuction was associated with higher improvement in health-related quality of life compared with no treatment. However, the associated data were not reported to enable an independent corroboration of this finding, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(163 reference statements)
0
1
0
Order By: Relevance
“…6 Subramonian and Farrah, in their study on the overall psychiatric or behavioral adverse effects of levetiracetam, suggested an improvement in symptoms with brivaracetam treatment. 7 The FDA has warned about the possible adverse effects of brivaracetam, namely, irritability, depression, aggressive behavior, and anxiety. Behavioral side effects of the drug have been reported.…”
Section: Tablementioning
confidence: 99%
“…6 Subramonian and Farrah, in their study on the overall psychiatric or behavioral adverse effects of levetiracetam, suggested an improvement in symptoms with brivaracetam treatment. 7 The FDA has warned about the possible adverse effects of brivaracetam, namely, irritability, depression, aggressive behavior, and anxiety. Behavioral side effects of the drug have been reported.…”
Section: Tablementioning
confidence: 99%